The Practice of Executing Wasiat Distribution of Assets from Perspective of the Compilation Islamic Law in Prambonwetan Village, Rengel District, Tuban Regency - Yudi Arianto; Hawa’ Hidayatul Hikmiyah; Chamidah Alawiyah (Institut Agama Islam Nahdlatul Ulama Tuban, 2025)
In the practice of wasiat distribution property in Prambonwetan, wasiat are commonplace for people to manage their property after death. Because wasiat is said to be the last mandate of a person which is carried out after the owner dies. Everyone has full rights to the property they own. But in Prambonwetan village there are conflicts between families caused by unfair wasiat because they are not in accordance with Islamic law or the provisions in the KHI. The formulation of the problem in this study is twofold, namely: (1) How is the practice of implementi wasiat in Prambonwetan village? (2) How is the review of the Compilation of Islamic Law on the implementation of wasiat in Prambonwetan village? The objectives of this study are as follows (1) To examine how wasiat are practiced in Prambonwetan village. (2) To find out how the review of the Compilation of Islamic Law This research method uses a qualitative approach, namely a research method that produces analytical descriptive data. With the type of empirical legal research. The data collected and the findings of this study use technical triangulation, namely combining two data collection techniques, namely interviews and documentation. The results of field research on the implementation of wasiat in Prambonwetan village do not use the guidelines of the Compilation of Islamic Law, wasiat are carried out informally without following the official procedures regulated in the Compilation of Islamic Law. Wasiat are made verbally without notary approval. In practice, there is a distribution of assets exceeding one-third of the assets owned so that it is not in accordance with Article 195 KHI paragraph 2 and Article 201 KHI because the heirs do not agree to the existence of a will exceeding one-third of the assets left behind.